Speckle Tracking Echocardiography of the Right Atrium: The Neglected Chamber - Rai, Aitzaz Bin Sultan (Clin Cardiol, 2015)
The right atrium (RA) plays a pivotal role in electromechanical and endocrine regulation of the heart. Its peculiar anatomical features and phasic mechanical function make it distinct from ventricles. Various invasive and noninvasive techniques have been used to elucidate RA structure and function. Of these modalities, echocardiography has distinct advantages over others. Several conventional measures of RA function through echocardiography have been described in the literature, but they are load dependent. A relatively new technique is speckle tracking–derived strain, which is relatively less dependent on loading conditions. Speckle tracking echocardiography tracks acoustic scatters (speckles) of myocardium frame‐by‐frame to calculate strain or deformation of the myocardium. Speckle tracking echocardiography has been used extensively for strain assessment of the right and left ventricle to detect subtle disease pathology, to gain mechanistic insight, as a marker of ischemic metabolic memory, as an endpoint in clinical trials, and as a functional assessment tool. The RA is a relatively neglected chamber, as it is mostly studied for assessment of atrial mass lesions, for electrophysiological studies, and in animal models for physiological assessment. However, its role in the systolic and diastolic function of the right heart, pulmonary vascular pathology, congenital heart diseases, and combined electromechanical activation phenomena has been less explored or unexplored. Speckle tracking echocardiography is an ideal tool for the assessment of the RA because of its regional and global functional characterization, angle independence, and high temporal resolution.